Применение метода сечений для контроля формы поверхности пятна излучения в реальном времени - Кутаев, Ю.Ф.; Тимченко, Л.И.; Кокряцкая, Н.И.; Губернаторов, В.А.; Поплавский, А.А. (Інститут проблем штучного інтелекту МОН України та НАН України, 2009)
В статье рассматривается проблема контроля формы поверхности пятна излучения в реальном времени.
Предлагается использование метода сечений для формирования выборки и последующей обработки
дальнейших изображений. У статті розглядається проблема контролю форми поверхні плями випромінювання у реальному часі.
Пропонується використання методу перетинів для формування вибірки і наступної обробки подальших
зображень. Now in polygraphy, laser processing of materials, a location, optical communication and other areas of
engineering necessity of wider implantation of optically-electronic systems with automatic adjustment of
distortions of formed light radiation is felt. Destabilising effect of mechanical or climatic factors, instability
of characteristics of a source of radiation, indignation in an optical path can be the reasons of these
distortions, in preliminary adjustment optical units, etc. Support of comprehensible quality of correction
demands continuous runtime check of characteristics of light radiation, for example space allocation of its
intensity, including an estimation of deviation of the specified allocation from initial or standard allocation.
In the given operation theoretical bases on solution of the given problem are considered, the modelling which
results are presented.